Consolidation problems in freight transportation systems: mathematical models and algorithms - Castellucci, Pedro Belin (2019)
Freight distribution systems are under stress. With the world population growing, the migration of people to urban areas and technologies that allow purchases from virtually anywhere, efficient freight distribution can be challenging. An inefficient movement of goods may lead to business not being economically viable and also has social and environmental negative effects. An important strategy to be incorporated in freight distribution systems is the consolidation of goods, i.e., group goods by their destination. This strategy increases vehicles utilisation, reducing the number of vehicles and the number of trips required for the distribution and, consequently, costs, traffic, noise and air pollution. In this thesis, we explore consolidation in three different contexts (or cases) from an optimisation point of view. Each context is related to optimisation problems for which we developed mathematical programming models and solution methods. The first case in which we explore consolidation is in container loading problems (CLPs). CLPs are a class of packing problems which aims at positioning three-dimensional boxes inside a container efficiently. The literature has incorporated many practical aspects into container loading solution method (e.g. restricting orientation of boxes, stability and weight distribution). However, to the best of our knowledge, the case considering more dynamic systems (e.g. cross-docking) in which goods might have a schedule of arrival were yet to be contemplated by the literature. We define an extension of CLP which we call Container Loading Problem with Time Availability Constraints (CLPTAC), which considers boxes are not always available for loading. We propose an extension of a CLP model that is suitable for CLPTAC and solution methods which can also handle cases with uncertainty in the schedule of the arrival of the boxes. The second case is a more broad view of the network, considering an open vehicle routing problem with cross-dock selection. The traditional vehicle routing problem has been fairly studied. Its open version (i.e. with routes that start and end at different points) has not received the same attention. We propose a version of the open vehicle routing problem in which some nodes of the network are consolidation centres. Instead of shippers sending goods directly to their consumers, they must send to one of the available consolidation centres, then, goods are resorted and forwarded to their destination. For this problem, we propose a mixed integer linear programming model for cost minimisation and a solution method based on the Benders decomposition framework. A third case in which we explored consolidation is in collaborative logistics. Particularly, we focus on the shared use of the currently available infrastructure. We defined a hub selection problem in which one of the suppliers is selected as a hub. In a hub facility, other suppliers might meet to exchange their goods allowing one supplier to satisfy the demand from others. For this problem, we propose a mixed integer linear programming model and a heuristic based on the model. Moreover, we compared a traditional distribution strategy, with each supplier handling its demand, against the collaborative one. In this thesis, we explore these three cases which are related to consolidation for improving the efficiency in freight distribution systems. We extend some problems (e.g. versions of CLP) to apply them to a more dynamic setting and we also define optimisation problems for networks with consolidation centres. Furthermore, we propose solution methods for each of the defined problems and evaluate them using randomly generated instances, benchmarks from the literature and some cases based on real-world characteristics.